Implementing pharmacogenetic testing in fluoropyrimidine-treated cancer patients: DPYD genotyping to guide chemotherapy dosing in Greece - Ragia, Georgia; Maslarinou, Anthi; Atzemian, Natalia; Biziota, Eirini; Koukaki, Triantafyllia; Ioannou, Charalampia; Balgkouranidou, Ioanna; Kolios, George; Kakolyris, Stylianos; Xenidis, Nikolaos; Amarantidis, Kyriakos; Manolopoulos, Vangelis G. (Frontiers in Pharmacology, 2023)
Introduction: Dihydropyrimidine dehydrogenase (DPD), encoded by DPYD gene, is the ratelimiting enzyme responsible for fluoropyrimidine (FP) catabolism. DPYD gene variants seriously affect DPD activity and are well validated predictors of FP-associated toxicity. DPYD variants rs3918290, rs55886062, rs67376798 and rs75017182 are currently included in FP genetic-based dosing guidelines and are recommended for genotyping by the European Medicines Agency (EMA) before treatment initiation. In Greece, however, no data exist on DPYD genotyping. The aim of the present study was to analyze prevalence of DPYD rs3918290, rs55886062, rs67376798, rs75017182, and, additionally, rs1801160 variants, and assess their association with FP-induced toxicity in Greek cancer patients. Methods: Study group consisted of 313 FP-treated cancer patients. DPYD genotyping was conducted on QuantStudio ™ 12K Flex Real-Time PCR System (ThermoFisher Scientific) using the TaqMan® assays C__30633851_20 (rs3918290), C__11985548_10 (rs55886062), C__27530948_10 (rs67376798), C_104846637_10 (rs75017182) and C__11372171_10 (rs1801160). Results: Any grade toxicity (1-4) was recorded in 208 patients (66.5%). Out of them, 25 patients (12%) experienced grade 3-4 toxicity. DPYD EMA recommended variants were detected in 9 patients (2.9%), all experiencing toxicity (p=0.031, 100% specificity). This frequency was found increased in grade 3-4 toxicity cases (12%, p=0.004, 97.9% specificity). DPYD deficiency increased the odds of grade 3-4 toxicity (OR: 6.493, p=0.014) and of grade 1-4 gastrointestinal (OR: 13.990, p=0.014), neurological (OR: 4.134, p=0.040) and nutrition/metabolism (OR: 4.821, p=0.035) toxicities. FP dose intensity was significantly reduced in DPYD deficient patients (β=-0,060, p<0.001). DPYD rs1801160 variant was not associated with FP-induced toxicity or dose intensity. Triple interaction of DPYD*TYMS*MTHFR was associated with grade 3-4 toxicity (OR: 3.725, p=0.007).: Our findings confirm the clinical validity of DPYD reduced function alleles as risk factors for development of FP-associated toxicity in the Greek population. Pre-treatment DPYD genotyping should be implemented in clinical practice and guide FP dosing. DPYD*gene interactions merit further investigation as to their potential to increase the prognostic value of DPYD genotyping and improve safety of FP-based chemotherapy.